2016
DOI: 10.1097/ftd.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring, Electronic Health Records, and Pharmacokinetic Modeling to Evaluate Sirolimus Drug Exposure–Response Relationships in Renal Transplant Patients

Abstract: Background Sirolimus, an immunosuppressant agent used in renal transplantation, can prevent allograft rejection. Identification of the therapeutic index (ratio of minimum toxic concentration to minimum therapeutic concentration) for immunosuppresants is necessary to optimize the care of patients and set standards for bioequivalence evaluation of sirolimus products. However, the therapeutic index for sirolimus has been inconsistently defined, potentially due to inconsistencies in sirolimus exposure-response rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…To date, a number of population PK/PD modelling studies have been published for sirolimus, mostly in patients after renal transplantation. [33][34][35][36][37][38][39][40][41] As part of these studies several predictors of clearance were identified, including body size (ie body weight), hematocrit and CYP3A5 genotype. 33,35,38 Djebli et al developed a Bayesian estimator as part of sirolimus dose individualization using a practical three-time point limited sampling strategy with samples at pre dose, 1 and 3 hours post dose.…”
Section: Implementation Of Mipdmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a number of population PK/PD modelling studies have been published for sirolimus, mostly in patients after renal transplantation. [33][34][35][36][37][38][39][40][41] As part of these studies several predictors of clearance were identified, including body size (ie body weight), hematocrit and CYP3A5 genotype. 33,35,38 Djebli et al developed a Bayesian estimator as part of sirolimus dose individualization using a practical three-time point limited sampling strategy with samples at pre dose, 1 and 3 hours post dose.…”
Section: Implementation Of Mipdmentioning
confidence: 99%
“…These studies are not only the investigations using a pharmacometrics approach to characterize sirolimus PK/PD. To date, a number of population PK/PD modelling studies have been published for sirolimus, mostly in patients after renal transplantation 33–41 . As part of these studies several predictors of clearance were identified, including body size (ie body weight), hematocrit and CYP3A5 genotype 33,35,38 .…”
Section: Introductionmentioning
confidence: 99%
“…However, sirolimus has a long half-life, a narrow therapeutic window, and large individual variations in the pharmacokinetics 8 and therefore, its improper use may cause adverse reactions, such as immune rejection, thrombocytopenia, leucopenia, or hyperlipidemia. 9,10 Immunosuppressive drugs in the body are usually measured once or twice a day before the patient is given a new dosage 11 and it is, therefore, important to monitor their blood levels for the duration of any treatment. In addition, a rapid and efficient monitoring method for sirolimus should allow its quantification in human whole blood, because it is mainly distributed in erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have described the population pharmacokinetic (PopPK) characteristics of sirolimus in pediatric patients, [9][10][11][12] pharmacokinetic data for children with TSC are still limited. 13,14 In addition, the therapeutic range for oral sirolimus is narrow, and the apparent clearance and apparent volume of distribution (V d ) are highly variable in pediatric patients, 9 which might lead to treatment failure or increased drugrelated toxicity.…”
mentioning
confidence: 99%